35 - OBESITY, DEPRESSION IN SCHOOLCHILDREN AND THEIR RELATIONSHIP WITH PHYSICAL ACTIVITY (Fiep Bulletin - online, 2022)
The current lifestyle and family and social dynamics have changed considerably, affecting daily habits and the emotional core of the family, transcending symptomatically in its smallest members. Emerging feelings of emptiness, such as the need to consume excessively unhealthy foods or be subjected to a life of contemplation. The purpose of this work is to show the prevalence of overweight - obesity (S-O) associated with symptoms of depression and its relationship with physical activity (A-F). Material and methods: 352 adolescents, 133 men and 218 women participated, with an age of 12.1 ± 1 years, body weight of 54 ± 14 kg, 52 ± 11 kg, height 157 ± 12 cm and 156 ± 7 cm men and women respectively. The level of overweight-obesity (S-O) was determined through the BMI and level of physical activity by the Physical Activity Questionnaire (CAF) 1, modified for adolescents, the presence of depression (D) was evaluated, using the CDI. Results. 14% of the adolescents presented symptoms of depression, 8% men and 6% women. The S-O was significantly higher in depressed girls (63%) and 100% inactive vs. non-depressive (30%) and 7% active, not so in men where the highest amount of S-O (52%) was observed in non-depressive vs. depressives (51%). In addition to a higher A-F in the non-depressed (7%) vs. depressives (0%), (p> 0.05). Discussion and conclusion The prevalence of depression in men is the same in both S-O and normal weight. Not so in women where the highest prevalence of S-O is that of depressed girls.